PENGARUH MEMBACA 5 MENIT SEBELUM BELAJAR TERHADAP MINAT BACA SISWA PADA PEMBELAJARAN BAHASA INDONESIA - Melti Tiara; Sukardi; Noviati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to see and determine the effect of reading 5 minutes before studying on students' reading interest in learning Indonesian. This study uses a quantitative method, consisting of 2 variables, namely the independent variable (free variable), namely reading five minutes before studying (X) and the dependent variable (bound variable), namely students' reading interest (Y). quasi-experimental design approach or pseudo-experiment. This study will use a one group pretest and posttest design research design. Research results Based on the results of the One-Sample Test with Test Value = 0, a t value of 35.287 was obtained with a degree of freedom (df) of 47. The results of this test also showed a significance value (Sig. 2-tailed) of 0.000, which is smaller than the level of significance commonly used (α = 0.05). In addition, the Mean Difference value of 28.792 indicates a significant difference between the conditions before and after students carried out the short reading activity. The 95% Confidence Interval range for this average difference is at 27.15 to 30.43, which indicates that the difference is not only significant but also consistent, so it can be concluded that the null hypothesis (H0) is rejected and Ha is accepted. It can be concluded that there is a significant influence between the 5-minute reading activity before studying on increasing students' reading interest in learning Indonesian.